Mortality and survival in nonagenarians during the COVID-19 pandemic: Unstable equilibrium of aging - Kashtanova, Daria A.; Erema, Veronika V.; Gusakova, Maria S.; Sutulova, Ekaterina R.; Yakovchik, Anna Yu.; Ivanov, Mikhail V.; Taraskina, Anastasiia N.; Terekhov, Mikhail V.; Matkava, Lorena R.; Rumyantseva, Antonina M.; Yudin, Vladimir S.; Akopyan, Anna A.; et al. (Frontiers in Medicine, 2023)
In the present study, we identified predictors of one-year mortality in a cohort of long-living individuals. Additionally, since the study coincided with the COVID-19 pandemic, we were able to determine risk factors for severe COVID-19-related morality. All participants aged 90 and older (median=92) underwent a two-stage comprehensive geriatric assessment, extensive blood testing and survey with a one-year follow-up. We recruited 2020 participants; however, after the second stage, full sets of data were only available for 1641 participants. The most reliable predictors of overall mortality were cognitive impairment, malnutrition, frailty, and aging-associated diseases as well as their markers in blood serum: decreased levels of protein fractions, iron, 25-hydroxyvitamin D, high-density lipoprotein, IGF-1, proinflammatory markers, and N-terminal pro b-type natriuretic peptide level. We also built a predictive model of overall mortality in the long-living individuals (f-score=0.76). In the recovered COVID-19-patients, the most significant mortality predictors were depression, frontal lobe dysfunction, frailty, high α1-globulin levels, N-terminal pro b-type natriuretic peptide level, initially high white blood cell and neutrophils counts, lowered 25-hydroxyvitamin D, IGF-1, and high-density lipoprotein. Hence, the most sensitive and reliable predictors of mortality in our study were the risk factors that could be modified with proper geriatric care and support. For instance, treating nutritional deficiencies, vitamin D supplementation and timely prevention of cognitive decline could promote positive health outcomes in individuals in their “golden years”.